Gajah Mada Sang Maha Patih Pemersatu Nusantara di Bawah Majapahit Tahun 1336 M - 1359 M - Agus Susilo; Andriana Sofiarini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study is to find out the history of the Elephant Maiden of the United States National Guard. This research uses the History method by collecting primary and secondary sources. Research results During the Wuruk Chicken, the Majapahit Kingdom experienced a peak of success thanks to the role of Patih Amngkubhumi Elephant Mada, which was marked by the oath of Amukti Palapa to establish a unification of the Archipelago. The Majapahit Kingdom knot is one of the largest Kingdoms in the archipelago. At the time of the success of the Majapahit kingdom under the leadership of King Hayam Wuruk, the Majapahit became prosperous and had a very successful period. Obviously the Mada elephant reciting his Oath which is known by the name of Amukti Palapa. Relying on good military and political strategies, Mahapatih Elephant Mada was able to apply his Palatine oath, making him the most respected duke in the Majapahit Kingdom and in other territories. Keywords: Gajah Mada, Archipelago, Majapahit